Rengat Lakeside Resort Dengan Pendekatan Eco-tech Architecture - Muhammad Hidayatullah; Gun Faisal; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Rengat is the capital of Indragiri Hulu Regency which has several tourist attractions. One of the most frequently visited tourist objects is Raja Lake which is located on Jalan Sultan Rengat. The location of the lake is quite strategic because it is in the city of Rengat. The lake has enormous potential and has quite number of visitors. However, there are several things that have resulted in reduced visitors. Some of the factors causing the reduced number of visitors to Raja Lake Tourism Object are caused by unmet requests or needs of visitors. For this reason, the quality of the tourism area can be improved by providing those that can meet various recreational needs in a design. The resort design is an appropriate design to advance the Raja Lake tourism object and increase the economic income of Rengat City. In designing this resort on Raja Lake, it requires a design approach that prioritizes aesthetics and comfort for visitors while still paying attention to environmental balance. The right design is Eco-Tech Architecture, which is a design approach that links and harmonizes the environment and is based on concerns about global environmental conservation with an approach to land use energy management and effective waste management in architectural architecture. Keywords: Eco-Tech Architecture, Raja Lake, Rengat, Resort